Feedback from a European Bioanalysis Forum survey on bioanalysis of drugs in tissues. (June 2014) - Mokrzycki, Nathalie; Delrat, Pascal; Meulder, Marc De; Erbach, Eva; Lenthéric, Irene; McIntosh, Morna; Dzygiel, Pawel; Timmerman, Philip
Tissue analysis has always been a difficult discipline of bioanalysis. Laboratories that perform bioanalysis in tissue are facing a lot of challenges and questions before starting experiments, from a scientific/technical point of view regarding more regulated aspects. Actually, literature is poor regarding the more technical and scientific aspects but also beyond that no clear guidance is available on this topic and laboratories performing tissue analysis face real ambiguity regarding regulatory requirements, always with the risk of under- or over-validation of the assay. For all of these reasons bioanalysis in tissue became a frequently discussed topic within the European Bioanalytical Forum (EBF) organization. The EBF then decided to treat this as a specific topic, and carried out a survey that was done in two steps between 2012 and 2013. This paper represents an exhaustive summary of the result of this survey that includes themost important aspects of tissue bioanalysis. This survey provided the team a good starting point for their discussions and resulted in an EBF recommendation paper published separately.